Designing the user interface : strategies for effective human-computer interaction - Shneiderman, Ben.; Plaisant, Catherine (Boston : Addison-Wesley, 2010)
'Designing the User Interface' provides a comprehensive, authoritative introduction to the dynamic field of human-computer interaction (HCI). Students and professionals learn practical principles and guidelines needed to develop high quality interface designs - ones that users can understand.
Introduction. Usability of interactive systems ; Guidelines, principles, and theories -- Development processes. Managing design processes ; Evaluating interface designs -- Interaction styles. Direct manipulation and virtual environments ; Menu selection, form fill-in, and dialog boxes ; Command and natural languages ; Interaction devices ; Collaboration and social media participation -- Design issues. Quality of service ; Balancing function and fashion ; User documentation and online help ; Information search ; Information Visualization -- Societal and individual impact of user interfaces. Future interfaces ; Ten plagues of the information age ; Continuing controversies.
Includes bibliographical references and indexes.
Buku bacaan asas fakulti
Keywords: Human-computer interaction; User interfaces (Computer systems).